ϒ(nS) polarizations versus particle multiplicity in pp collisions at s√= 7 TeV - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Asilar, E.; Bergauer, T.; Brandstetter, J.; Brondolin, E.; Dragicevic, M.; Erö, J.; Fabjan, C.; Flechl, M.; et al. (My University, 2016)
The polarizations of the ?(1S), ?(2S), and ?(3S) mesons are measured as a function of the charged particle multiplicity in proton–proton collisions at View the MathML source. The measurements are performed with a dimuon data sample collected in 2011 by the CMS experiment, corresponding to an integrated luminosity of 4.9 fb?1. The results are extracted from the dimuon decay angular distributions, in two ranges of ?(nS) transverse momentum (10–15 and 15–35 GeV), and in the rapidity interval |y|<1.2. The results do not show significant changes from low- to high-multiplicity pp collisions, although large uncertainties preclude definite statements in the ?(2S) and ?(3S) cases.
Citation: Khachatryan, V., Sirunyan, A. M., Tumasyan, A., Adam, W., Asilar, E., Bergauer, T., . . . Woods, N. (2016). ?(nS) polarizations versus particle multiplicity in pp collisions at s=7 TeV. Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 761, 31-52. doi:10.1016/j.physletb.2016.07.065
Keywords: Cms; Physics; Qcd Medium Effects; Quarkonium Polarization; Quarkonium Production